Vizag port traffic study (Note) - Ramani, K.V.; Mishra, Gouri Shankar (2001)
The ports in the country have been making periodical efforts to streamline their cargo handling capacity and system. The present study focuses on the coal handling capacity of the vizag port that keeps going several steel plants and power stations across the eastern and southern parts of India. - Reproduced
Keywords: Note; Harbours